2014
DOI: 10.1016/j.otsr.2014.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Osteoid osteoma of the proximal femur: Treatment by percutaneous bone resection and drilling (PBRD). A report of 44 cases

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Navigation-assisted surgery for a benign bone tumor has been shown to be safe and useful for evaluating the location of deep benign bone tumors and confirming the position of tumors during curettage in real time [13]. A previous study reported that navigation assistance helped to successfully prepare small holes for the removal of deeply located osteoid osteomas [14]. Although the tumors were small and deep in some of our patients (#2, 4 and 5), the navigation system helped to successfully detect the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Navigation-assisted surgery for a benign bone tumor has been shown to be safe and useful for evaluating the location of deep benign bone tumors and confirming the position of tumors during curettage in real time [13]. A previous study reported that navigation assistance helped to successfully prepare small holes for the removal of deeply located osteoid osteomas [14]. Although the tumors were small and deep in some of our patients (#2, 4 and 5), the navigation system helped to successfully detect the tumors.…”
Section: Discussionmentioning
confidence: 99%
“…After the tumor is removed, the bone cortex can be replanted, and the healing is very fast. In other studies, pathological fracture and limited bone union were the main complications of the surgical treatment of OO, with an incidence rate of up to 8% [9,24]. Ruiz et al [25] reported that among 26 patients with bone tumors treated by radiofrequency ablation, one had symptomatic bone infarction, and another one had a pathological fracture.…”
Section: Resultsmentioning
confidence: 99%
“…OO is a benign bone tumour with pain as the rst symptom accompanied by evident nocturnal pain and typical intra-cortical nidus surrounded by sclerosis and cortical thickening as the primary manifestation, which often requires surgical intervention [3,6,[21][22][23]. The proximal femoral constitutes the most susceptible part for OO, which is challenging to treat because of its deep location, close to the hip joint, and complex local anatomy [4,14,15,17,24].…”
Section: Discussionmentioning
confidence: 99%